2019
DOI: 10.1080/10942912.2019.1607374
|View full text |Cite
|
Sign up to set email alerts
|

Probing the physicochemical and sensorial properties of pasteurized milk via nanoparticles

Abstract: The present study was conducted to evaluate the effects of storage time and temperature on physicochemical and sensory properties and to measure the spoilage of pasteurized fluid milk stored at different temperatures via nanoparticles on pasteurized fluid milk. The mean values for pH of milk samples decreased (from 6.81 to 6, 5.46, and 4.37), acidity increased (10%, 21%, and 35%), fat contents decreased (13%, 24%, and 32%), protein contents decreased (7%, 18%, and 24%), lactose contents decreased (5%, 7%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…(2005) for isoflavone‐enriched dairy milk while the results for overall acceptability scores are in close agreement with the findings of Rashid et al. (2019) in pasteurized milk.…”
Section: Resultssupporting
confidence: 89%
“…(2005) for isoflavone‐enriched dairy milk while the results for overall acceptability scores are in close agreement with the findings of Rashid et al. (2019) in pasteurized milk.…”
Section: Resultssupporting
confidence: 89%
“…71 The use of nanotechnology during the pasteurization process can help food manufacturers prevent the uncontrolled growth of pathogens. 73 Nanomaterials that are used indirectly or directly in processing are:…”
Section: Pasteurizationmentioning
confidence: 99%
“…76 4. Silicon oxidein studies carried out by A. Rashid, 73 it was shown that silica nanoparticles can be used to monitor the stability of pasteurized milk through the colorimetric detection of volatile substances. Moreover, SiO 2 may act as a nanosensor to detect volatile compounds produced by bacteria in psychrotrophic milk spoilage at cooling temperatures.…”
Section: Pasteurizationmentioning
confidence: 99%
See 1 more Smart Citation